CRITICAL THINKING TEST DEVELOPMENT of THE SUMATIVE FINAL SEMESTER (SAS) ENGLISH at MTs (ISLAMIC JUNIOR HIGH SCHOOL) as BANK of ENGLISH TEST BASED ON GOOGLE FORM - Rahman, M. Saufi; Riffani, M.; Mukarramah, Mukarramah (STKIP Persada Khatulistiwa Sintang, 2025)
This study develops a critical thinking assessment for the Summative Final Semester (SAS) English Exam at Madrasah Tsanawiyah (MTs). The goal of study to know the quantitative characteristic of critical thinking test of Summative Final Semester (SAS) using google form. This study a Research and Development approach, test items were designed based on the curriculum and validated by experts. Trials test were conducted with 120 students to know difficulty, discriminant, validity, and reliability by statistical. The results indicated while students performed well on language proficiency tasks, they faced challenges with critical thinking questions, emphasizing the need for more comprehensive preparation in this area. Values of expert validation is more 0,78, validation items is > 0,3, reliability is 0.92, difficulty is easy, medium and hard, and discriminant is good. The digital platforms used Google Forms to create interactive assessments, not only measure language skills but also assess and develop critical thinking.